Simulation technologies in training interns and continuing professional education of practicing anesthesiologists - Bielka, Kateryna; SmirnovaМariya; Fomina , Hanna (The Ukrainian Scientific Medical Youth Journal, 2023)
the responsibility for the work of vital functions, which falls on the anesthesiologist during manipulations, requires a high level of skills, especially in critical situations, therefore the introduction and expansion of modern innovative training methods is the key to a constant increase in the quality of training of specialist doctors. In the field of anesthesiology, simulation trainings, as a tool for learning and evaluating acquired knowledge and skills, are used both for practicing doctors, applicants for post-graduate education, and for students of medical universities. The inclusion of the latest training methods, expansion of the base of technical capabilities for cadets ensures high-quality and effective training of medical personnel before the start of their clinical practice, which is a guarantee of safety for patients and a reduction of the burden on the health care system due to a decrease in the percentage of complications that arise as a result of the human factor. Reducing the number of complications that may arise due to the insufficient level of training of specialists has a beneficial effect on the health care system as a whole. Improvements in the form of control of acquired skills and competences make it possible to qualitatively and quickly identify errors and correct them. At the Department of Surgery, Anesthesiology and Intensive Care of the University named after O.O. Bogomolets is widely used in a variety of educational programs, including seminars, modeling situations and practicing technical skills using mannequins and anesthesia equipment, telesimulation training using video equipment (televisions, cameras, projectors, tablets). Studying and improving modeling techniques, increasing the material and technical base for training, expands opportunities for introducing the latest treatment methods into clinical practice. The success of the development of anesthesiologists requires constant improvement of existing methods and the development of the latest technologies and training methods based on promising developed algorithms. The introduction of simulation technologies and virtual reality technologies, as well as their adaptation to modern requirements and refinement of already existing simulators, has great potential for the development of technologies for training anesthesiologists all over the world. Expanding the network of training centers will help to increase the number of anesthesiologists in general. In the future, optimizing simulation programs will depend on a clear understanding of what can and cannot be achieved with different simulation models and hardware.